Investigation on Poly(2-Oxybutane-1-yl(4-Oxynapthalene-1- yl)Sebacoylate Random Block Copolyester - Elango , G.; Guhanathan , S. (Current Innovations in Chemical and Materials Sciences Vol. 4, 2024)
Synthesis of random block copolymer i.e., Poly(2-oxybutane-1-yl(4-oxynapthalene-1- yl)Sebacoylate [PONS] was synthesized using 1,4-napthalenediol, 1, 2-butane diol and sebacoylchloride. Formation of copolyester was confirmed using UV, FTIR, NMR spectral techniques. Thermal studies were carried out using TGA. Elemental analysis and gel permeation chromatography further confirm the formations of the copolymer and the molecular weight of the copolyester. The morphology of the copolyester was also characterized using SEM. The results of the investigation clearly encourage the synthesis of such a thermally stable copolyester in the field of copolyester for specific applications.